ASPIRE Academy for Sports Excellence - Qatar (2011)
The Vison of the Qatar Institute ist to become the leading elite sports institute in the world. It drives active sporting healthy lifestyles for the people of Qatar. It is recognized for state-of-the-art sports science. World class coaches and sport scientists work with ASPIRE student-athletes to give them the opportunity to become sport champions, the hearts of their junior and senior national teams. The ASPIRE education curriculum is designed for university preparation and is aligned with SEC standards, offering a foundational and advanced program to meet each individual student`s needs and his potential for academic success. ASPIRE community programs change the daily lives of Qatar`s people by making a sporting, healthy, and active lifestyle accessible and promoting a sporting culture. Currently there are approximately 200 student-athletes in grades 7 through 12 who specialize in the sports of football, athletics, squash, table tennis, sailing, judo, gymnastics, swimming, tennis, fencing, rowing, shooting and golf. Football, athletics, squash and table tennis are considered "main sports" in which the Academy provides a full-time coaching staff and year round training program. The remaining sports are called "federation sports" in which the Academy provides strength and conditioning programs, performance enhancement and other sports science services, medical services and Academy schooling but the athletes are coached by coaches in their respective national sport federation. The ASPIRE sports program depends on a comprehensive talent identification testing program and is fully supported by state-of-the-art sports science services, a strength and conditioning program, and excellent medical and health services.